Women in Contemporary Irish Theatre: Widening the Space - Illingworth, Ruth (Hungarian Journal of English and American Studies, 2020)
Book review:Haughton, Miriam, and Mária Kurdi, eds. Radical Contemporary Theatre Practices by Women in Ireland. Dublin: Carysfort Press, 2015. 251 pages. ISBN 978-1-909325-75-3. Pbk. €20.